A model-based approach for the calibration and traceability of the angle resolved scattering light sensor. (19th April 2016) - Seewig, Jörg; Eifler, Matthias; Schneider, Frank; Kirsch, Benjamin; Aurich, Jan C
Abstract: Within the field of geometric product specification there is a growing need for the application of inline measurement systems. The use of inline measurement requires robust and fast measurement principles. A very robust optical measurement principle is the angle resolved scattering light (ARS) sensor. The ARS sensor provides high precision and high resolution measurement data of technical surfaces because the surface angles are measured as an intensity distribution on a detector instead of measuring a series of discrete height values. However, until now, there were no specific measurement standards for the calibration of the ARS sensor and no traceability was ensured. In this paper, new strategies for the calibration of an ARS sensor are proposed. A new mathematical model for the ARS sensor is introduced. Based on this, two new measurement standards for the calibration of the sensor parameters are derived. These standards are designed with a model-based approach and can calibrate sensor-specific properties of the ARS sensor. The manufacturing of the standards is described and measurement results are provided.